Effective uric acid reduction with probenecid and febuxostat in a patient with chronic kidney disease. (31st January 2018) - Case, Robert; Wentworth, Brian; Jester, Grant
Abstract : A 33-year-old male with poorly controlled chronic tophaceous gout and chronic kidney disease (CKD) with estimated glomerular filtration rate (GFR) of 37 cc/min. His uric acid was 11 mg/dL despite maximal dosing of febuxostat. He had previously failed pegloticase infusions as well. This patient had a reduction in his uric acid level to less than 6 mg/dL following addition of probenecid to his febuxostat regimen. Most guidelines recommend against utilisation of probenecid therapy in patients with GFR <50, but there is no obvious contraindication to its use, provided renal calculi do not develop. Our case illustrates the synergistic effect probenecid can add to maximal xanthine oxidase inhibitor therapy for patients with refractory hyperuricaemia in a patient with CKD stage IIIb. With the approval of a new uricosuric medication, lesinurad, probenecid may remain a suitable alternative for patients with financial limitations to achieve target uric acid levels.